Pengujian Limbah Air Tahu Terhadap Jumlah Stomata dan Kandungan Klorofil Tanaman Kedelai Hitam (Glycine soja L. ) - Idris, M.; Rahmadina, Rahmadina (JURNAL AGROPLASMA, 2022)
The purpose of this study become to determine the impact of giving tofu waste water on the content material of chlorophyll and stomata in black soybean (Glycine soja L.). The studies became conducted from August to October 2021 at Pantai Labu. Jl. Burhanuddin Dusun 1 Deli Serdang Regency. Analysis of chlorophyll content material and stomata at Plant physiology Laboratory of USU. The substances use have been black soybean (Glycin soja L.), EM4 550 ml, 5 liter tofu waste water, 200 ml molasses, 400 gr brown sugar. The tools used are paranet, 20 liter water drier, measuring cup, filter, polybag, soil, ruler, pen, label paper, meter and pH indicator. Variabelobservation Â have been the number of stomata, chlorophyll content measured at the end of the generative phase at 30 days after planting. Calculation of the number of stomata changed into performed the use of a photomicograph the usage of freshly sliced preparations at the suggestions of the leaf shoots, whilst the analysis of chlorophyll content material became accomplished the usage of acetone solvent.This study used non-factorial randomized block design (RCBD). The treatment is Tofu Water Waste (K) at four stage, K0 = 0%, K1 = 15%, K2 = 20%, K3 = 25% with 3 times replication. The analysis data usedStatistical Product and Service Solutions (SPSS) version 20 on the one way ANOVA test with a significant level of 5% and continued with the Duncan Multiple Range Test Â (DMRT). The results showed that the provision of tofu waste water had no significant effect at the number of stomata and the amount of exact chlorophyll determined in leaf sampling in multiples of three (young leaf), 5 (middle leaf), and 8 (old leaf) from the top of leaf tip. Visually, the pleasant treatment for the number of stomata in K3 (25% concentration of tofu water waste) via taking leaf samples in multiples of 5 (young leaf) from the tip of the leaf shoot. meanwhile, the amount of chlorophyll in K1 is tofu water waste at a concentration of 15% through taking leaf samples in multiples of 8 (old leaf) from the end of the leaf shoot.Keywords: wastewater tofu, number of stomata, chlorophyll content, black soybean